In Vitro and In Vivo Supramolecular Modification of Biomembranes Using a Lipidated Coiled‐Coil Motif1. Issue 52 (8th November 2013) - Zope, Harshal R.; Versluis, Frank; Ordas, Anita; Voskuhl, Jens; Spaink, Herman P.; Kros, Alexander
<x xml:space="preserve">Abstract</x> Superficial appeal: The surface of live cells and zebrafish embryos can be modified by a supramolecular method. A peptide pair that forms a coiled coil at the cell membrane can be used to dock liposomes in in vitro and in vivo environments (see scheme). This tool can be used in biophysical studies of biological processes occurring at membranes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>